Development and Psychometric Properties of a Questionnaire to Assess Iranian Women's Sexual Self-disclosure - Raziyeh Maasoumi; Sedigheh Rashedi; Samira Noorzaei (Hamadan University of Medical Sciences, 2024)
Background and Objective: Sexual self-disclosure plays an important role in couples' sexual performance and satisfaction. It is necessary to have a valid, reliable tool to measure this variable. A review of the literature shows that there is no tool with socio-cultural appropriateness for Iranian women in this field. Therefore, the purpose of this research was to design and evaluate the psychometric properties of a context-based female sexual self-disclosure questionnaire. Materials and Methods: This methodological study was conducted in Tehran city in 2020. In the first phase, the sexual self-disclosure of Iranian women and its dimensions was explored by reviewing the literature using the thematic analysis approach. Then, using the deductive-inductive approach, the first 25 items were compiled. In the second phase, psychometric assessment was done by examining face, content, construct, and criterion validity, as well as internal consistency and test-retest reliability. Results: According to the results, sexual self-disclosure of Iranian women was extracted as "talking about sexual relationships and factors affecting quantity and quality." Quantitative indicators for content validity index and content validity ratio were 0.95 and 0.79, respectively. The results of examining the construct validity of the tool by exploratory factor analysis led to the identification of four factors that explained 65.06 of the variances. The assessment of the convergent validity indicated the correlation coefficients between the total score of this questionnaire and the Larson Sexual Satisfaction Questionnaire in the range of 0.66 to 0.93. Conclusion: The results showed that women's sexual self-disclosure questionnaire had optimal validity and reliability. Therefore, it is suggested to use this instrument in future studies to assess the level of Iranian female's sexual self-disclosure.